Array - Amalia, Iqlyma; Wahyuningsih, Fahmi (LATERNE, 2024)
This development research is motivated by the need for the development of innovative and interactive learning media in German language learning activities in phase F of the independent learning curriculum. This is known based on the results of pre-action interviews with German language teachers at SMAN 15 Surabaya. Based on these problems, the purpose of this research is to develop a learning media snakes and ladders 3D Pop Up Box with the theme Mahlzeiten (food) for German speaking skills in phase F. In addition, the purpose of this study was to determine the feasibility of the snakes and ladders 3D Pop Up Box media. The research model used is R&D (Research and Development) by Dick and Carey. The stages in this research are Analysis, Design, and Development. The data collection instrument used is an expert validation sheet. Experts used to test the feasibility of developing this media are material experts, media experts, and expert practitioners. The results of the media feasibility test get a percentage of 76% from material experts, then get a percentage of 93% from practitioners, and a percentage of 97.33% from media experts. Thus it can be concluded that the learning media snakes and ladders 3D Pop Up Box is very feasible to use as a learning media for German language classes phase F.